Effects of acute caffeine, theanine and tyrosine supplementation on mental and physical performance in athletes - Zaragoza, J.; Tinsley, G.; Urbina, S.; Villa, K.; Santos, E.; Juaneza, A.; Tinnin, M.; Davidson, C.; Mitmesser, S.; Zhang, Z.; Taylor, L. (Journal of the International Society of Sports Nutrition, 2019)
Background: A limited amount of research has demonstrated beneficial effects of caffeine and theanine supplementation for enhancement of mental performance. The purpose of this investigation was to determine whether the acute ingestion of a supplement containing caffeine, theanine and tyrosine improves mental and physical performance in athletes. Methods: Twenty current or former male collegiate athletes (age: 20.5 ± 1.4 y; height: 1.82 ± 0.08 m; weight: 83.9 ± 12.6 kg; body fat: 13.8 ± 5.6%) completed this randomized, double-blind, placebo-controlled crossover trial. After familiarization, each participant completed two identical testing sessions with provision of a proprietary dietary supplement (SUP) containing caffeine theanine and tyrosine or a placebo (PL). Within each testing session, participants completed assessments of mental and physical performance before and after provision of SUP or PL, as well as after two rounds of exercise. Assessments were performed using a performance testing device (Makoto Arena) that evaluated multiple aspects of mental and physical performance in response to auditory and visual stimuli. Testing was performed both with the body in a static position and during dynamic movement. General linear models were used to evaluate the effects of SUP and PL on performance. Results: Changes in movement accuracy during performance assessment were greater following SUP ingestion as compared to PL for both static and dynamic testing (SUP: + 0.4 to 7.5%; PL: - 1.4 to 1.4% on average; p < 0.05). For dynamic testing, the change in number of targets hit was higher and the change in average hit time was lower with SUP as compared to PL (p < 0.05). However, there were no differences between conditions for the changes in number of targets hit or average hit time during static testing. There were no differences in changes of subjective variables during either condition, and performance measures during the two rounds of exercise did not differ between conditions (p > 0.05). Discussion: The present results indicate that a combination of a low-dose of caffeine with theanine and tyrosine may improve athletes` movement accuracy surrounding bouts of exhaustive exercise without altering subjective variables. Based on this finding, supplementation with caffeine, theanine and tyrosine could potentially hold ergogenic value for athletes in sports requiring rapid and accurate movements.